Post-translational Modifications of IκBα: The State of the Art - Wang, Xiuli; Peng, Hanlin; Huang, Yaqian; Kong, Wei; Cui, Qinghua; Du, Junbao; Jin, Hongfang (Frontiers in Cell and Developmental Biology, 2020)
The nuclear factor-kappa B (NF-κB) signaling pathway regulates a variety of biological functions in the body, and its abnormal activation contributes to the pathogenesis of many diseases, such as cardiovascular and respiratory diseases and cancers. Therefore, to ensure physiological homeostasis of body systems, this pathway is strictly regulated by IκBα transcription, IκBα synthesis, and the IκBα-dependent nuclear transport of NF-κB. Particularly, the post-translational modifications of IκBα including phosphorylation, ubiquitination, SUMOylation, glutathionylation and hydroxylation are crucial in the abovementioned regulatory process. Because of the importance of the NF-κB pathway in maintaining body homeostasis, understanding the post-translational modifications of IκBα can not only provide deeper insights into the regulation of NF-κB pathway but also contribute to the development of new drug targets and biomarkers for the diseases.